2004
DOI: 10.1002/ajh.20043
|View full text |Cite
|
Sign up to set email alerts
|

R147W mutation of PROC gene is common in venous thrombotic patients in Taiwanese Chinese

Abstract: We analyzed the genetic defects of 21 unrelated patients with venous thrombosis in whom hereditary protein C deficiency was diagnosed. Eleven mutations were detected in 18 families, while no mutation was detectable in the other three families. Among these mutations, a common genetic mutation of protein C (PROC) gene recurred in 43% (nine propositi from these 21 families). This C6152T mutation at exon 7 resulted in a missense mutation, Arg147Trp (R147W). Each propositus or family carrier had another specific po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 19 publications
1
23
2
Order By: Relevance
“…F139V has been found in the PC deficiency pedigrees of Chinese and Japanese (Miyata et al, 1996;Zhou et al, 2007). D255H has also been reported in patients with PC deficiency and venous thrombosis (Tsay and Shen, 2004). The family members with the D255H heterogeneous mutation had lower levels of PC:A and PC:Ag compared to those members with F139V, suggesting that the D255H mutation impacts the quantity of PC more significantly.…”
Section: Discussionmentioning
confidence: 92%
“…F139V has been found in the PC deficiency pedigrees of Chinese and Japanese (Miyata et al, 1996;Zhou et al, 2007). D255H has also been reported in patients with PC deficiency and venous thrombosis (Tsay and Shen, 2004). The family members with the D255H heterogeneous mutation had lower levels of PC:A and PC:Ag compared to those members with F139V, suggesting that the D255H mutation impacts the quantity of PC more significantly.…”
Section: Discussionmentioning
confidence: 92%
“…10 The p.R147W mutation in the PROC gene, a type 2 PC deficiency, is found to be common among Asian populations. 14,15 The present study demonstrated p.R147W as a common mutation in the Thai population. The prevalence rates of heterozygous and homozygous p.R147W, among 690 volunteers, were 5.8% and 0.1%, respectively.…”
Section: Discussionmentioning
confidence: 92%
“…. Large vessel thrombosis, including renal vein thrombosis, has been reported in some infants 13) . Pur pura fulminans is triggered by infection, trauma, and even minor decreases in levels of therapeutic anticoagulants 14,15) .…”
Section: Case Reportmentioning
confidence: 99%